Joint (stimulus) control: um recurso conceitual para análise comportamental da resolução de problemas - Regis Neto, Denigés Maurel (2016)
The work takes the view that the Joint Control is a contribution to the analysis of Problem-solving behavior, especially in solving logical problems. Introducing the Skinner's analysis Problem Solving and its gaps in Study 1, and the notion of Joint Control in Study 2, the thesis is supported in Study 3 with the analysis of the links between the elements of the Joint Control and problem solving. Study 3 shows how codic and transformational responses, and multiple control of a response (Joint Control) contribute to our understanding of the precise performances Matching to Sample (MTS), MTS itself as a problem situation in which resolution-responses are part of the necessary behavior to the assignment, identification of controls present in the flow of problem-solving responses; their participation in the formulation and confirmation of mathematical problem solving; in the development and control by rules, ; and, lastly, the possibilities of controls that act on the listener's behavior on strengthen and agree with the speaker